Dynamic Behavior of Materials. Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics /: Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics. Volume 1 : (2018) - Unknown
No abstract available